How to Recognize an Adult When You Meet One? : Adultness in the Novel Minoes and Its Film Adaptation - van Lierop-Debrauwer, Helma (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
Children learn about the cultural meanings of age and aging from the people in their environment but also from the media. In an era in which the different life stages are understood as a continuum rather than separate categories, age socialization has probably become more complicated than ever before, making the role of the mediators—children’s books and flms included—especially important. This article explores the mediation of aging in Minoes (1970), a children’s book by Annie M. G. Schmidt—the most famous Dutch author of children’s books—and compares its age ideology to that of the flm adaptation, which appeared in 2001. The comparison is set against the background of changes over the last ffty years in how aging is perceived within Western societies. Both in the book and in the flm, this analysis shows, the model of standard adulthood is under revision. Instead of representing a fxed age identity, adulthood is portrayed as being as much a process of becoming as childhood is, as it is characterized by inner growth and making individual choices. Although the similarities between book and flm are more striking than the differences, the flm’s adult protagonists are slightly more capable of making their own decisions than those in the book; this difference mirrors the ongoing shift towards a changing perception of adultness that had only just started when the book was published in 1970.